Iowa Birdline update, January 15, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for January 15, 1990. Highlights of the update include sightings of a Townsend's Solitaire, Eurasian Tree Sparrows, Short-eared Owls, and 25 Snow Buntings. Also of note was the continued presence of 3 Long-eared Owls and a sighting of a Pileated Woodpecker at a suet feeder. Epson - sheet feed/flatbed